Seventy Percent of Abstracts Presented at the AANA Annual Meeting Are Later Published - Tyson Stoker, M.S; Brandon Klein, D.O., M.B.A; Lucas E. Bartlett, D.O; Benjamin Millar, B.S; Randy M. Cohn, M.D; Nicholas A. Sgaglione, M.D (Elsevier, 2024)
Purpose: To assess the future publication rates of abstracts presented at AANA annual meetings between 2015 and 2019. Methods: Abstracts presented at the 2015-2019 AANA annual meetings were identified. The PubMed and Google Scholar databases were searched for a corresponding manuscript for each abstract using the name of the first author, abstract title, and keywords. A level of evidence and anatomic category were assigned to each abstract. For each corresponding manuscript identified, the authors, journal of publication, journal impact factor (IF), time to publication, and number of citations were recorded. Results: Overall, 70.5% of abstracts presented at the 2015-2019 AANA annual meetings (275 of 390) went on to future publication, with 63.6% (248 of 390) achieving publication within 3 years. The median time to publication from presentation was 12.8 months. Arthroscopy (29.8%) was the most frequent journal of publication. The average IF of publishing journals was 4.92 ± 3.41, with 61.8% of manuscripts (170 of 275) published in journals with an IF of at least 4.00. Published manuscripts received an average of 36.30 ± 47.6 citations per manuscript. A stronger level of evidence was associated with an increased likelihood of future publication (P = .008). Conclusions: Pre-publication literature presented at the AANA annual meetings has continued to be associated with a strong likelihood of future publication in Arthroscopy and Arthroscopy, Sports Medicine, and Rehabilitation, as well as other respected peer-reviewed journals. Clinical Relevance: Exposure to pre-publication literature may have an impact on clinical management. It is important to understand the quality of research presented in abstracts from AANA annual meetings. Knowing how many abstracts are ultimately published in peer-reviewed journals provides an indicator of the quality and reliability of the research.